Design and Implementation of Low Voltage Power Communication System Based on Single Frequency Communication - Peiling ZHANG; Keke ZHAO (Zhongguo dianli)
In order to improve the reliability of low voltage power line communication, a low voltage power line carrier single frequency communication system is proposed, which integrates the single frequency communication and low-voltage power line communication. Based on the physical layer of Q/GDW 11612—2016 standard, the system only needs to modify the data link layer, thus shortening the signal propagation time. At the same time, a fractional PLL based interval clock synchronization algorithm is proposed to avoid the excessive adjustment of the clock and realize the high-precision adjustment of the single frequency communication clock synchronization in the system. The simulation and actual measurement results show that the proposed clock synchronization algorithm has high clock accuracy; and the low voltage power line carrier single frequency communication system has a higher communication reliability compared with power line communication due to its integration of the complementary advantages of the two. It can be seen that the low-voltage power line carrier single frequency communication system is practical and reliable.